Raw deal how the "Uber economy" and runaway capitalism are screwing American workers - Hill, Steven 1958- (St. Martin's Press, 2015)
"Every day, innovative entrepreneurs pioneer bold economic ideas that change the way we live and work. Companies like Google, Apple, Oracle, Facebook and Twitter aren't the only ones shaping our economic future...there's another trend emerging that will change the ways we work and live. The "sharing economy," or the "collaborative consumption economy," includes companies like TaskRabbit, Airbnb, Uber, Lyft, Zaarly, and DocVacay who are purveyors of an economic system that revolves around sharing human and physical resources. This new aspect to the economy, Steven Hill argues, is a dead end for U.S. workers, as well as for the national economy.In Raw Deal, Hill shows the "sharing economy" is a new and troubling component to what is an overall bad economy that undermines workers. Vulnerable freelancers and day laborers hire themselves out for ever smaller jobs and amounts of money, and it is only the companies who hire them who reap the big benefits. Hill argues that we must shift the support for American workers to one that is individual-based rather than workplace-based. Countering the onset of the freelance society and the new economy is the new civil rights and labor struggles of our time. This important book answers these questions and provides pragmatic solutions to adapt our economic system to its new realities, launching a new civil rights struggle capable of transforming the freelance society into a stakeholder society"...